A Juridical Analysis of Regulations and Polemics in a Regulation Concerning Higher Education’s Sexual Harassment - Abraham Ethan Martupa Sahat Marune (Indonesian Journal of Multidisciplinary Science, 2021)
This research aims to analyze the rule of law and polemics in Permendikbudristek No. 30 of 2021 on Prevention and Handling of Sexual Violence in the College Environment. So in this study will examine the first,how is the urgency of the issuance of Permendikbudristek No. 30 of 2021 on Handling Sexual Violence Second,What are the arrangements and polemics in Permendikbudristek No. 30 of 2021? This research uses normative juridical research methods and is qualitative. From the results of the study, it can be concluded that the establishment of regulations on the prevention of handling sexual violence in a college environment is very important given the high number of sexual harassment. Permendikbudristek 30/2021 regulates the prevention of sexual violence from learning, strengthening governance and culture & regulating the handling of sexual violence from mentoring to victim recovery. There are several polemics that arise from this rule. However, existing rejections and polemics tend to be based on a misguided understanding of context as straightened out in this study. It is expected that Permendikbudristek Number 30 of 2021 can be earnestly applied by universities throughout Indonesia and in its implementation needs supervision from the relevant ministries.